Pelatihan Pengelolaan Manajemen SDM Untuk Meningkatkan Kinerja Tenaga Pendidikan - Muhammad Atha Iqbal; Masbullah; Salmi Yuniar Bahri; Moh. Juhad; Sandy Ari Wijaya (Jurnal Pelayanan Masyarakat, 2024)
The title of this activity is "Training on Human Resource Management to Improve the Performance of Educational Personnel," conducted at SMK Lowis Sakti. The objective of this activity is to provide guidance and counseling to the Principal, Vice Principal, Administrative Staff, and Teachers of SMK Lowis Sakti regarding the basic concepts of human resource management. This counseling aims to enhance their understanding and knowledge. The implementation of this activity involves several stages, including the survey and socialization stages. During the survey stage, preparations were made by organizing the materials, setting the schedule for delivery, and conducting a survey of the activity location. Before the activity was carried out, a socialization stage was conducted, involving an initial meeting to explain the purpose and objectives of this activity to the SMK Lowis Sakti team, as well as to establish a schedule for cooperation and activities. The execution team for this activity consists of six lecturers from the Public Administration Program of ITSKes Muhammadiyah Selong. The materials presented by the community service team cover topics such as Human Resource Management, Management, Human Resource Management Concepts, Reward Systems, Education Quality, and Performance.